Raman Microspectroscopic Analysis of Selenium Bioaccumulation by Green Alga Chlorella vulgaris - Kizovský, Martin; Pilát, Zdeněk; Mylenko, Mykola; Hrouzek, Pavel; Kuta, Jan; Skoupý, Radim; Krzyžánek, Vladislav; Hrubanová, Kamila; Adamczyk, Olga; Ježek, Jan; Bernatová, Silvie; Klementová, Tereza; et al. (Biosensors, 2021)
Selenium (Se) is an element with many commercial applications as well as an essential micronutrient. Dietary Se has antioxidant properties and it is known to play a role in cancer prevention. However, the general population often suffers from Se deficiency. Green algae, such as Chlorella vulgaris, cultivated in Se-enriched environment may be used as a food supplement to provide adequate levels of Se. We used Raman microspectroscopy (RS) for fast, reliable, and non-destructive measurement of Se concentration in living algal cells. We employed inductively coupled plasma-mass spectrometry as a reference method to RS and we found a substantial correlation between the Raman signal intensity at 252 cm-1 and total Se concentration in the studied cells. We used RS to assess the uptake of Se by living and inactivated algae and demonstrated the necessity of active cellular transport for Se accumulation. Additionally, we observed the intracellular Se being transformed into an insoluble elemental form, which we further supported by the energy-dispersive X-ray spectroscopy imaging.
Keywords: selen; Selenium; algae; ICP-MS; Bioaccumulation; bioaccumulation; Water Pollutants, Chemical; Spectrum Analysis, Raman; EDX; Chlorella vulgaris; selenium; chemické látky znečišťující vodu; Ramanova spektroskopie; bioakumulace; Raman spectroscopy